Logistics sprawl in monocentric and polycentric metropolitan areas: the cases of Paris, France, and the Randstad, the Netherlands - Heitz, Adeline; Dablanc, Laetitia; Tavasszy, Lorant A. (REGION, 2017)
The phenomenon of urban sprawl has been studied extensively. Most research so far has focused on residential settlements. A growing number of studies have addressed industrial deconcentration. Our focus in this paper is on logistics sprawl, i.e. the growth and suburban relocation of warehousing activities. Specifically, we investigate the difference in logistics sprawl between monocentric and polycentric systems of cities. The literature suggests that logistics activities, like residential settlements, will gradually move to suburbs as land prices increase in central areas. As research for logistics has mostly focused on monocentric systems, the question is whether this also applies to polycentric systems. We compare two cases, the Paris region in France, representative of a monocentric development, and the Dutch Randstad area as a polycentric case. We use regional statistics on warehouse settlements in both regions for a descriptive analysis of changes since the mid 2000s to derive metrics for concentration. The cases show different patterns of change in concentration. In contrast to Paris, logistics activities within the Randstad have intensified in dense areas. We explore the reasons that may explain this difference and conclude that urban structure, spatial planning policies and the freight hub quality of a region are factors of influence.